A fluorescence biochip with a plasmon active surface - Matthews, DR; Summers, H; Njoh, K; Chappell, S; Errington, R; Smith, P; Pope, I; Barber, P; Vojnovic, B; Ameer-Beg, S (2007)
We present details of the development of a optical biochip, with integrated on-chip laser excitation, for fluorescence intensity cell based assays. The biochip incorporates an "active surface" for the control and manipulation of fluorescent species placed directly on the device. The active elements of the biochip are one-dimensional periodic sub-wavelength corrugations fabricated on a thin gold film. We have made fluorescence intensity measurements of both an organic dye (Cy5), and immobilized and fluorescently labeled (with 705 nm emitting quantum dots), mammalian tumor cells in contact with the active surface. Here we show that the presence of the periodic grating can be used to control both the excitation and fluorescence generation process itself. We demonstrate that the gratings convert evanescent surface optical modes into well-defined beams of radiation in the far-field and at the surface of the device this produces highly contrasting regions of fluorescence excitation providing regions of high spatial selectivity.